2019
DOI: 10.1097/aud.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

Do Personality Factors Assessed Before Cochlear Implantation Predict Hearing-Related Quality Of Life After Cochlear Implantation in Postlingually Deafened Adults?

Abstract: While significant improvement of hrQoL was seen 12 months after implant activation, this improvement was barely predicted by the Big-Five personality traits measured before implantation. Only Neuroticism was found to moderately influence postimplantation hrQoL in our patients, in the way that higher degrees of Neuroticism tend to go along with lower degrees of self-esteem (as conceptualized by the NCIQ). The failure to detect personality effects on hrQoL could partly be due to the low levels of Extraversion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
1
4
0
5
Order By: Relevance
“…The relationships between personality traits, choice of coping, and QoL have been studied among patients with cochlear implants (CI). Muigg and colleagues [ 25 ] found that hearing related QoL improved in patients receiving CI, and furthermore, the QoL scores were affected by neuroticism. Cox et al have reported that personality traits seem to be associated with reported hearing problems both before and after the fitting of hearing aids (HA).…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between personality traits, choice of coping, and QoL have been studied among patients with cochlear implants (CI). Muigg and colleagues [ 25 ] found that hearing related QoL improved in patients receiving CI, and furthermore, the QoL scores were affected by neuroticism. Cox et al have reported that personality traits seem to be associated with reported hearing problems both before and after the fitting of hearing aids (HA).…”
Section: Introductionmentioning
confidence: 99%
“…osobowościowych czy związanych ze zdrowiem psychicznym osób głuchych (lub słabosłyszących), którym został wszczepiony implant ślimakowy. Wciąż nieliczne badania na ten temat dotyczą użytkowników CI wyłącznie z głuchotą nabytą postlingwalnie [1][2][3]. Jak dotąd nie pojawiły się doniesienia naukowe dotyczące badań, których celem byłoby poznanie psychologicznych uwarunkowań percepcji korzyści i satysfakcji z CI u dorosłych użytkowników z głuchotą prelingwalną [4].…”
Section: Wstępunclassified
“…w sferze ograniczeń w podejmowanej aktywności (NCIQ -AL) oraz interakcji społecznych (NCIQ -SI). Korzyści w tych sferach są na takim poziomie jak u użytkowników CI z częściową głuchotą [32], lecz większe niż w przypadku tych, którzy słuch utracili postlingwalnie i korzystają z CI od 12 miesięcy [2]. Najmniejszych korzyści z CI badani doświadczają w sferze psychologicznej (NCIQ -SE), co jest wynikiem podobnym do wyników osób z częściową głuchotą o początku prelingwalnym [32], ale są to znacząco większe korzyści niż u osób z głuchotą postlingwalną (tabela 3).…”
Section: Percepcja Korzyści Z Implantu śLimakowego (Nciq)unclassified
See 2 more Smart Citations